"There's more love between us": The parental experience of attending Mellow Babies, a targeted, early intervention program for parents and their babies. Issue 1 (15th December 2022) - Davidson, Ciera; Raouna, Aigli; Malcolm, Ruaridh; Ibrahim, Raquib; MacBeth, Angus
Abstract: It is recognized that parenthood in the context of psychosocial adversity can have negative implications for infant development. Parenting programs are the first line of intervention to improve outcomes for families; however, evidence for the effectiveness of group‐based, targeted early interventions is still scarce. Preliminary findings indicate Mellow Babies (MB) as a promising group‐based parenting program for families at risk for parenting difficulties. Using thematic analysis, we aimed to understand: (i) the aspects of the intervention that enabled parents to complete the program and (ii) the relational and behavioral changes perceived as valuable for parents and their babies post‐intervention. In total, 68 parents residing in the United Kingdom were interviewed after completing MB (49 mothers and 19 fathers; 88% self‐identified as British). Three themes and six subthemes were generated from the data. Parents identified several intervention components as beneficial, including the facilitators' interpersonal skills and multi‐dimensional, group‐based approach. Participant reflections highlighted three underlying mechanisms that enabled positive change: (i) the sense of community cultivated within the group, (ii) the process of formulating and re‐conceptualizing one's difficulties, and (iii) the opportunity to reshape interpersonal interactions. Findings are discussed within the context of perinatal and infant mental health. Resumen: Se reconoce que la paternidad/maternidad dentro del contexto de la adversidad sicosocial puede tener implicaciones negativas para el desarrollo del infante. Los programas sobre la crianza son la línea frontal de intervención para mejorar los resultados para las familias, sin embargo, la evidencia para la eficacia de las intervenciones tempranamente identificadas, con base en el grupo, es escasa. Los resultados preliminares indican que Bebés Apacibles (Mellow Babies / MB) es un prometedor programa de crianza con base en el grupo para familias bajo riesgo de dificultades en la crianza. Haciendo uso de análisis temáticos, nos propusimos comprender: i) los aspectos de la intervención que les permite a los progenitores completar el programa y ii) los cambios relacionales y de comportamiento que se percibieron como valiosos para los progenitores y sus bebés con posterioridad a la intervención. En total, se entrevistaron 68 progenitores residentes del Reino Unido después de completar MB (49 mamás y 19 papás; 88% autoidentificados como británicos). De la información surgieron tres temas y seis subtemas. Los progenitores identificaron como beneficiosos varios componentes de la intervención, incluyendo las habilidades interpersonales de quienes facilitaban la participación y el acercamiento multidimensional con base en el grupo. Las reflexiones de los participantes subrayaron tres mecanismos subyacentes que permitieron el cambio positivo: i) el sentido de comunidad cultivado dentro del grupo; ii) el proceso de formular y reconceptualizar las propias dificultades; y iii) la oportunidad de volver a darle forma a las interacciones interpersonales. Los resultados se discuten dentro del contexto de la salud mental perinatal y del infante. Résumé: On reconnaît généralement que la parentalité dans le contexte d'adversité psychosociale peut avoir des implications négatives pour le développement du bébé. Les programmes de parentage sont la première ligne d'intervention afin d'améliorer les résultats pour les familles. Cependant les preuves de l'efficacité d'interventions précoces ciblées et basées sur un groupe sont encore rares. Des résultats préliminaires indiquent que Bébés d'humeur joyeuse, Mellow Babies (MB) est un programme de parentage basé sur un groupe prometteur pour les familles à risque de difficultés de parentage. En utilisant une analyse thématique nous nous sommes donné pour but de comprendre: i) les aspects de l'intervention qui permettent aux parents de finir le programme et ii) les changements relationnels et comportementaux qui sont perçus comme étant précieux pour les parents et leurs bébé après l'intervention. Au total 68 parents résidant au Royaume Uni ont été interviewés après avoir terminé le programme MB (49 mères et 19 pères; 88% s'étant auto‐identifiés comme britanniques). Trois thèmes et six sous‐thèmes ont émergé des données. Les parents ont identifié plusieurs composantes de l'intervention comme étant bénéfiques, y compris les compétences interpersonnelles du facilitateur ou de la facilitatrice et son approche multi‐dimensionnelle, basée sur un groupe. Les réflexions des participants ont mis en lumière trois mécanismes sous‐jacents qui permettait un changement positif: i) le sens de communauté cultivé au sein du groupe; ii) les processus de formulation et de ré‐conceptualisation de ses propres difficultés; et iii) l'opportunité de refaçonner les interactions interpersonnelles. Les résultats sont discutés dans le contexte de la santé mentale du nourrisson et périnatale. Zusammenfassung: "Da ist mehr Liebe zwischen uns": Erfahrungen von Eltern mit der Teilnahme an „Mellow Babys", einem gezielten Frühförderprogramm für Eltern und ihre Babys Es ist bekannt, dass Elternschaft im Kontext von psychosozialen Widrigkeiten negative Auswirkungen auf die Entwicklung von Säuglingen haben kann. Elternprogramme sind die erste Anknüpfungsstelle, um Outcomes für Familien zu verbessern, doch gibt es bisher nur wenig Wirksamkeitsbelege für gruppenbasierte, gezielte Frühinterventionen. Vorläufige Ergebnisse deuten darauf hin, dass „Mellow Babies" (MB) ein vielversprechendes gruppenbasiertes Elternprogramm für Familien mit einem Risiko für Erziehungsschwierigkeiten ist. Mithilfe einer thematischen Analyse wollten wir zwei Dinge besser verstehen: i) Welche Aspekte der Intervention versetzen die Eltern dazu in der Lage, das Programm abzuschließen, und ii) Welche Beziehungs‐ und Verhaltensänderungen werden nach der Intervention für die Eltern und ihre Babys als wertvoll empfunden wurden. Insgesamt wurden 68 Eltern mit Wohnsitz in Großbritannien nach dem Abschluss von MB interviewt (49 Mütter und 19 Väter; 88 % gaben an, Briten zu sein). Aus den Daten ergaben sich drei Themen und sechs Unterthemen. Die Eltern bezeichneten mehrere Komponenten der Intervention als hilfreich, darunter die zwischenmenschlichen Fähigkeiten der Moderator:in und den multidimensionalen, gruppenbasierten Ansatz. In den Reflexionen der Teilnehmenden wurden drei zugrundeliegende Mechanismen hervorgehoben, die positive Veränderungen ermöglichten: i) Das in der Gruppe kultivierte Gemeinschaftsgefühl, ii) der Prozess der Formulierung und Neukonzeption eigener Schwierigkeiten; und iii) die Möglichkeit, zwischenmenschliche Interaktionen neu zu gestalten. Die Ergebnisse werden im Kontext der perinatalen und infantilen psychischen Gesundheit diskutiert. 抄録: "私たちの愛が深まった": 親と赤ちゃんのための焦点化された早期介入プログラム「Mellow Babiesメロウ ベイビーズ」に参加した親の体験 心理社会的逆境という文脈の中での子育ては、乳幼児の発達に悪影響を及ぼすと認識されている。子育て支援プログラムは、家族の未来を改善するための介入手段の第一選択肢であるが、集団を基にしてターゲットを絞った早期介入の有効性を示す根拠はまだ乏しい。予備的知見では、メロウベイビーズ (MB) は、子育て困難のリスクを抱える家族向けの集団を基にした子育てプログラムとして有望であることが示された。我々は、テーマ分析を用いて、i) 親をプログラム修了に導いた、介入の側面、ii) 介入後に親とその赤ちゃんにとって価値があると認識された関係性と行動の変化、を理解することを目的とした。英国在住の68名の保護者 (母親49名、父親19名、88％が英国人と自認) に、MB終了後にインタビューを行った。その結果、3つのテーマと6つのサブテーマがデータから浮かび上がった。親は、ファシリテーターの対人関係スキルや多次元的な集団を基にしたアプローチなど、いくつかの介入要素を有益であると認識した。参加者の考察では、肯定的な変化を可能にする3つの基本的なメカニズムが強調された。i) グループ内で培われた共同体感覚、ii) 自分の困難を定式化し再認識するプロセス、iii) 対人相互交流を再形成する機会である。これらの知見は、周産期・乳幼児期のメンタルヘルスという文脈にそって議論されている。 摘要: 人们认识到, 在社会心理逆境中为人父母会对婴儿的发育产生消极影响。育儿计划是改善家庭发展结果的第一道干预线, 然而, 基于群体的、有针对性的早期干预措施有效性的证据仍然很少。初步研究结果表明, "成熟宝宝" (MB) 是一种很有前途的基于群体的育儿计划, 适用于有育儿困难风险的家庭。通过主题分析, 我们旨在了解:1) 使父母能够完成计划的干预措施;2) 在干预后被认为对父母及其婴儿有价值的关系和行为变化。总共有68位居住在英国的父母在完成MB后接受了采访 (49位母亲和19位父亲;88%的人自称是英国人) 。数据中归纳出三个主题和六个子主题。父母们确定了几个有益的干预因素, 包括辅导者的人际交往技能及其多维度、基于小组的方法。参与者的反映强调了促成积极变化的三个潜在机制:1) 群体内培养的社区意识;2) 阐述和重新概念化困难的过程;3) 重塑人际交往的机会。研究结果在围产期和婴儿心理健康的背景下进行了讨论。 ملخص: من المعروف أن الرعاية الوالدية في ظل الشدائد النفسية والاجتماعية يمكن أن يكون لها آثار سلبية على نمو الرضع. وتعتبر برامج التربية الوالدية هي خط التدخل الأول لتحسين النتائج للعائلات ، ومع ذلك ، لا تزال الأدلة على فعالية التدخلات المبكرة المستهدفة والمرتكزة على المجموعة نادرة. تشير النتائج الأولية إلى أن برنامج الأطفال اليانعين (Mellow Babies, MB) يعد برنامجًا واعدًا قائماً على المجموعة يختص بصعوبات التربية الوالدية وموجه للعائلات المعرضة للمخاطرة. باستخدام التحليل المواضيعي ، كنا نهدف إلى فهم 1) جوانب التدخل التي مكنت الآباء من إكمال البرنامج و 2) التغييرات العلائقية والسلوكية التي كانت ذات قيمة في نظر الوالدين وأطفالهم بعد التدخل. في المجموع ، تمت مقابلة 68 من الآباء والأمهات المقيمين في المملكة المتحدة بعد إكمال البرنامج (88 ٪ عرفوا بأنفسهم على أنهم بريطانيون). ظهرت ثلاثة مواضيع رئيسية وستة مواضيع فرعية من البيانات. حدد الآباء العديد من مكونات التدخل على أنها مفيدة ، بما في ذلك مهارات التواصل لمنسق البرنامج ونهج التدخل متعدد الأبعاد القائم على المجموعة. سلطت استجابات المشاركين الضوء على ثلاث آليات أساسية ساعدت على إحداث تغيير إيجابي: 1) الشعور بالمجتمع الذي ينمو داخل المجموعة ؛ 2) عملية صياغة وإعادة تصور الصعوبات الشخصية ؛ و 3) فرصة إعادة تشكيل التفاعلات الشخصية. يتم مناقشة النتائج في سياق الصحة النفسية في الفترة المحيطة بالولادة والرضع.